Paper ghosts [large type] : a novel of suspense - Heaberlin, Julia (Thorndike Press, a part of Gale, a Cengage Company, 2018)
"An obsessive young woman has planned since she was twelve--half her life--for this moment. Now she is almost certain the man who kidnapped and murdered her sister sits beside her. Carl Louis Feldman is a documentary photographer who may or may not have dementia--and may or may not be a serial killer. He claims no memory of it. Determined to find the truth, she lures him from a halfway house to propose a dangerous idea: a ten-day road trip to examine cold cases linked to his haunting photographs. Is he a pathological con artist? Or is she?"--Back cover.